Multimedia transmission using orthogonal frequency division multiplexing based on cognitive radio - 'Adli Husin, Hilmi Mujahid (2016)
With the rapid growth of multimedia applications over the wireless Internet, the demand for radio spectral resources has increased significantly. Referring to frequency spectrum allocations in Malaysia, major parts of spectrum have been assigned for government and commercial use. Despite the spectrum scarcity in meeting the demands for multimedia services, it was found from previous studies that most of the spectrum is actually not being utilised efficiently. Henceforth, lots of researches have been conducted to exploit this underutilised spectrum opportunistically without affecting the incumbents operations. Through the enabling Software Defined Radio (SDR) technology, Cognitive Radio (CR) has been proposed to solve the inefficient spectrum utilisation problems. CR is an adaptive, intelligent radio and network technology that has the ability to detect available vacant channels in radio frequency spectrum and change its particular transmission or reception parameters for efficient communication link achieved. In this thesis, SDR platform which consists of GNU Radio and Universal Software Radio Peripheral (USRP) is used for CR multimedia transmission development. In this system, adaptive Orthogonal Frequency Division Multiplexing (OFDM) is implemented to support robust multimedia transmission effectively. Next, Pseudorandom Multiband Frequency Switching is proposed for seamless frequency agility provision. For proof of concept, the proposed system is evaluated on several multimedia signals transmission. The results showed that the minimal time duration for each frequency switching of the system is approximately 1 second which resulted 20 dB for peak signal-to-noise ratio (PSNR) achievement. However, with higher rate of intermittent presence of incumbent or primary user (PU), faster switching rate is needed. Hence, the system developed needs further enhancement for a reliable and seamless multimedia transmission system to be realised.